Review Journals : Molecular From Anonaceae - Ilyas, Syafruddin (International Journal of Ecophysiology, 2023)
There are roughly 120 species of the Anona genus, which is found in tropical and subtropical areas. The diversity at the species level and similarity of the leaves, fruits, and stems that are produced as a result of plant cultivation and hybridization create new plants that are difficult to macroscopically identify. The diversity of the genus Anona can be accurately determined using molecular identification. For example, genetic analysis utilizing PCR and the RAPD and AFLP procedures is one way to gather molecular data. In this study, we inform the development of species-specific primers by differentiating the most agronomically interesting Annona species that, until recently, a new formal classification based on molecular phylogenetics has been developed in order to have a quick and precise method of distinguishing Annona between species agronomically.